Upaya Guru PAI dalam Pembentukan Karakter Sosial Siswa dalam Pendidikan di MTSN 2 Medan - Arlina, Arlina; Rini Amelia Siagian; Rina Susanti; Putri Rahayu Naibaho; Bilal Hafiz (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to explore the efforts of Islamic Religious Education (PAI) teachers in shaping the social character of students at Mtsn 2 Medan. Using a normative juridical approach, the research collected data through interviews, observations, and documentation. The findings indicate that social character formation is conducted through various methods, including the habituation of polite behavior, enforcement of discipline, use of distinctive terms between teachers and students to create emotional closeness, and the implementation of educational sanctions and rewards. These efforts collectively demonstrate the strategic role of PAI teachers in effectively and comprehensively shaping the social character of students.